Tatiana Brustin-Berenstein - Bańkowska, Aleksandra (Zagłada Żydów. Studia i Materiały, 2011)
A biographical sketch about Tatiana Brustin-Berenstein – a historian, long-standing employee of the Jewish Historical Institute, pioneer of historical research on the Holocaust in Poland, editor of Biuletyn Żydowskiego Instytutu Historycznego and Bleter far Geszichte, editor of historical sources for German occupation history.